(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2025)
Background. The design of coordination compounds using pyrazole-based ligands is of fundamental importance in contemporary materials chemistry due to their versatile coordination modes and diverse applications. Introducing trifluoromethyl groups onto such ligands is a powerful strategy to modulate the electronic and steric properties of the resulting metal complexes, significantly influencing their acidity, stability, and reactivity. In this context, 5-methyl-3-(trifluoromethyl)-1H-pyrazole stands out as a particularly promising ligand whose coordination chemistry with transition metals remains surprisingly underexplored. Despite its potential, a systematic investigation into the synthesis, structural diversity, and properties of its coordination compounds is largely absent from recent literature. This gap presents a missed opportunity, as the unique electronic profile of this ligand could unlock new functionalities in molecular materials. To address this, we present a comprehensive study on the synthesis and characterization of a new family of coordination compounds of first-row transition metals (Mn, Co, Ni, Cu, Zn) with the 5-methyl-3-(trifluoromethyl)-1H-pyrazole ligand. This work aims to systematically explore its coordination landscape, providing fundamental insights for the future design of advanced functional materials. Methods. In this work, the coordination compounds with transition metals were obtained using the 5-methyl-3-(trifluoromethyl)-1H-pyrazole ligand. A variety of techniques were used to identify and characterize the complexes and the ligand, including infrared, UV/Vis, and NMR spectroscopy, as well as microanalyses. Results. The interaction of 3d metals such as Mn(II), Co(II), Ni(II), Cu(II), and Zn(II) with 5-methyl-3-(trifluoromethyl)-1H-pyrazole in non-aqueous solutions was found to be solvent-dependent. In a solvent environment CH₃CN and CH₃OH (M(Ac)₂·4H₂O–L–CH₃OH/CH₃CN systems) at M:L ratios of 1:1 and 1:2, products with the composition M(Ac)₂·2L were formed. Meanwhile, in dimethylformamide (M(Ac)₂·4H₂O–L–DMF systems) under the same ratios, the complex Mn(Ac)₂·L·DMF, which incorporated a solvent molecule, was isolated. Conclusions. An organic ligand, 5-methyl-3-(trifluoromethyl)-1H-pyrazole, was synthesized. The interaction of 3d metals (M = Mn, Co, Ni, Cu, Zn) M(Ac)₂·xH₂O with 5-methyl-3-(trifluoromethyl)-1H-pyrazole in non-aqueous (CH₃CN, CH₃OH and DMF) solutions was investigated. Methods for the synthesis of Mn(II), Co(II), Ni(II), Cu(II), and Zn(II) compounds with 5-methyl-3-(trifluoromethyl)-1H-pyrazole were developed. Based on the data of elemental analysis and methods of IR, NMR, and electronic spectroscopy, the composition and structure of the obtained complexes have been proposed. It has been shown that in the obtained complexes: the most typical method of coordination of the pyrazole cycle is realized: monodentate - through the pyridine nitrogen atom; the formation of two types of mononuclear Mn(II), Co(II), Ni(II), Cu(II), and Zn(II) complexes is observed: M(Ac)2·2L and M(Ac)2·L·DMF; in the obtained complexes M(Ac)2·2L and M(Ac)2·L·DMF complexes, a six-coordinate environment of the central atom is realized due to four oxygen atoms from bidentate chelate coordinated acetate groups and two nitrogen atoms from molecules of a non-deprotonated ligand.